2020
DOI: 10.1111/bjh.16891
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of next‐generation sequencing compared to cytogenetics in patients with suspected myelodysplastic syndrome

Abstract: Summary Next‐generation sequencing (NGS) increasingly influences diagnosis, prognosis and management of myelodysplastic syndrome (MDS). In addition to marrow morphology and flow cytometry, our institution performs cytogenetics (CG) and NGS‐based testing routinely in patients with suspected MDS. We evaluated the relative value of NGS in the assessment of patients with suspected MDS. We initially compared the diagnostic and prognostic information derived from CG and NGS in 134 patients. NGS enhanced the diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…We also validated an "NGS first" testing algorithm to limit CG testing to cases with overt dysplastic changes on morphologic examination of the BM aspirate (BMA) or FCM. 5 In MDS, we and others demonstrated that NGS defined genetic abnormalities in more patients compared to CG. [5][6][7] Importantly, mutations or CG abnormalities were rarely detected in patients without dysplastic features or increased blasts.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…We also validated an "NGS first" testing algorithm to limit CG testing to cases with overt dysplastic changes on morphologic examination of the BM aspirate (BMA) or FCM. 5 In MDS, we and others demonstrated that NGS defined genetic abnormalities in more patients compared to CG. [5][6][7] Importantly, mutations or CG abnormalities were rarely detected in patients without dysplastic features or increased blasts.…”
Section: Introductionmentioning
confidence: 90%
“…5 In MDS, we and others demonstrated that NGS defined genetic abnormalities in more patients compared to CG. [5][6][7] Importantly, mutations or CG abnormalities were rarely detected in patients without dysplastic features or increased blasts. Likewise, Duncavage et al recently implemented a streamlined whole-genome sequencing (WGS) approach to assess patients with myeloid cancers.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…This process is used in most medical centers and clinical trials, especially to detect additional chromosome abnormalities and clonal evolution. Unfortunately, karyotyping is still laborious, expensive and time consuming[ 50 , 51 ].…”
Section: Diagnosismentioning
confidence: 99%
“…Thus, for some patients, molecular studies were more sensitive for clonal evolution than cytogenetic and FISH studies, concurring with a recent study of adults with cytopenias/suspected MDS. 39 The role of somatic panels in the diagnosis and treatment of patients with congenital or inherited cytopenias…”
Section: Somatic Mutations In Patients With Prolonged Cytopenias/ Suspected Mdsmentioning
confidence: 99%